2002
DOI: 10.1002/1099-0682(200203)2002:3<515::aid-ejic515>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

The Coordination of CuII in Zeolites − Structure and Spectroscopic Properties

Abstract: Keywords: Zeolites / Copper / Ab initio calculations / Density functional calculations / ESR spectroscopy / UV/Vis spectroscopy / Heterogeneous catalysis Zeolites loaded with transition metal ions are promising heterogeneous catalysts. Knowledge about the location and structure of the metal centers is of paramount importance for the understanding of the catalytic potential of these materials. In this work, the spectroscopic studies of the coordination of Cu II in zeolite A, ZK4, X, Y and mordenite are reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 128 publications
1
28
0
Order By: Relevance
“…Nevertheless, from comparison of the parameters shown in Table 2 with those reported in the bibliography for other Cu 2+ exchanged zeolites [37], signals A and B can be attributed to Cu 2+ in square pyramidal and square planar configurations, respectively. Figure 2b displays the spectrum recorded after the adsorption 2 molecules of C 3 H 8 per Cu atom on Cu-TNU-9.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, from comparison of the parameters shown in Table 2 with those reported in the bibliography for other Cu 2+ exchanged zeolites [37], signals A and B can be attributed to Cu 2+ in square pyramidal and square planar configurations, respectively. Figure 2b displays the spectrum recorded after the adsorption 2 molecules of C 3 H 8 per Cu atom on Cu-TNU-9.…”
Section: Resultsmentioning
confidence: 99%
“…In the work of Schoonheydt and co-workers,49-54 a set of Cu-containing zeolites was studied with UV-vis-NIR absorption and EPR spectroscopies. Examples of EPR spectra are shown in Figure 3, and the d-d transitions and EPR parameters of these Cu 2+ sites are summarized in Table 3.…”
Section: Coordination Of Tmi In Zeolite Channels and Cagesmentioning
confidence: 99%
“…A ligand field analysis of the d-d transitions of Co 2+ and Cu 2+ in six-ring sites indicated that the TMI are not symmetrically coordinated in the center of the ring, but undergo an off-axial displacement 55-58. Detailed ab initio quantum-chemical analysis revealed that coordination of Cu 2+ or Co 2+ in a specific exchange site leads to a strong site distortion 49, 51-54. First, the TMI try to maximize their coordination number.…”
Section: Coordination Of Tmi In Zeolite Channels and Cagesmentioning
confidence: 99%
“…24 It is well-known that Cu 2+ has a strong preference for a square planar coordination, and ab initio calculations on a copper complex in the six-ring plane have suggested that Cu 2+ is coordinated to three O(3) and one O(2), forming a distorted square plane. 10,13 Still, as long as Cu 2+ lies in the six-ring plane, the g z direction should be parallel to [111], contrary to our finding that it is tilted only 9°a way from the c axis. A trigonal complex with Cu 2+ displaced from the six-ring plane into the cage is more compatible with our finding.…”
Section: Discussionmentioning
confidence: 84%
“…[11][12][13] All EPR studies, however, have been carried out with powder samples, and g z directions of the copper species have never been determined experimentally. In ESEEM studies the g z directions of all species were assumed to be parallel to [111] of the cubic unit cell.…”
Section: Introductionmentioning
confidence: 99%